PENGUKURAN TINGKAT DERAJAT VIRTUALISASI PT. YANMAR DIESEL INDONESIA - Drajat Indrajaya (Faktor Exacta, 2011)
Information technology was grown with rapidly. In order to compete with the others corporation in global competition, so the corporation must adopt new structure which based on the idea of organizational modularization. Virtual corporation is a temporary network of independent companies, who combine their individual core competencies to optimize the process of value creation and who share costs, risks, resources, and the access to each other’s market. Keywords: information technology, virtual corporation, network..